(untitled) (Raparin Journal of Humanities (RJH), 2024)
The goal of this study is to, in theory, introduce the daily speech patterns of people in society in an unbiased manner, reflect these various patterns on the minds of other people, and then assess the results of the study. Theoretical aspects: To describe many styles of communication, such as the aesthetic style of speech (enthusiastic style), gentle speech style (normal), aggressive speech style and threatening speech style to present the notions of (style, speech, psychology). The following speech types are allotted: debate speech, polite speech, impolite speech, taboo speech, indirect communication, formal speech, and informal speech. Practical aspect: In this portion, the findings are examined once the research tool has been prepared, the research sample, the research community, and the tool’s reliability and stability have been established. Ranya’s six high schools were chosen at random. A total of (600) survey sheets were given out to high school students in both grades (10 and 11). One sample and two independent samples t test are used for the analysis.